Inhibitory effect of cow urine based plant extracts against Rhizoctonia solani causing sheath blight of rice - TIWARI*, R.K.S.; DAS, KUNTAL (Indian Phytopathology, 2011)
Seventeen medicinal plant extracts prepared in cow urine, hot water and cold water were evaluated in vitro and invivo against Rhizoctonia solani, the causal agent of sheath blight of rice. Irrespective of medicinal plants species, extractsprepared in cow urine were found significantly more efficacious in arresting the mycelial growth as well as in checking thedisease severity compared with cold water and hot water extracts. In vitro, cow urine based extracts of P. corylifolia and S.Â suaveolens were significantly more effective whereas, in vivo, extracts of P. corylifolia, A. racemosus and C. forskohlii werehighly efficacious and at par with hexaconazole. Moreover, cow urine extracts of C. gladiata, P. corylifolia and S. suaveolenswere more consistent and showed identical results under in vitro and in vivo.